Differential diagnostics of polymyalgia rheumatic in a university hospital in Finland - Suuronen, Saara (My University, 2023)
Polymyalgia rheumatica (PMR) is a common inflammatory disease that causes muscle pain and morning stiffness, almost exclusively affecting patients over the age of 50. PMR is most common in Scandinavian countries, which increases its clinical importance in northern Europe. The diagnosis of PMR is mainly clinical and based on symptoms and laboratory evidence of acute phase reaction, besides ruling out other conditions. Due to there being many other conditions that are presented with similar symptoms and findings, diagnosing PMR can be difficult. This study aimed to analyze how often the diagnosis of PMR changes during a follow-up period in a university hospital setting as well as determine the most common conditions misdiagnosed as polymyalgia rheumatica. All patients diagnosed with polymyalgia rheumatica during the years 2016-2019 were identified from the Turku University Hospital discharge register. The diagnosis was confirmed if the patient fulfilled at least one of five classification criteria for PMR, the clinical follow-up of at least 12 months was compatible with polymyalgia rheumatica and no other diagnosis better explained the patient’s condition. Out of the 374 patients analyzed in this study, 65.5% were considered to have polymyalgia rheumatica after further evaluation and clinical follow-up. The most common conditions initially misdiagnosed as polymyalgia rheumatica were inflammatory arthritides (34.9%), musculoskeletal disorders due to repetitive strain or degeneration (13.2%), infections (9.3%), malignancy (9.3%), giant cell vasculitis (6.2%) and other vasculitis (6.2%). In conclusion, the diagnosis of polymyalgia rheumatica is challenging and it is essential to consider the differential diagnostics carefully.
Keywords: polymyalgia rheumatica, PMR, differential diagnostics